Bali Home : Inspirational Design Ideas - Inglis, Kim; Photograph by Invernizzi, Luca (New York Tuttle Pub., 2009)
Bali is an island paradise that inspires countless dreams of tropical beaches, exotic people and gorgeous views. More than just an increasingly popular tourist destination, Bali is also a global leader in tropical design, showcased in all its glory in Bali Home . Covering over 100 homes, garden estates, hotels, restaurants and more, this book gives a tantalizing glimpse of the latest design trends coming out of Bali. Full-color photography, both of decorative details and architectural concepts, is accompanied by an insightful text that gives attainable interior design tips to tropical dream se.
Include Color Illustration
Keywords: Indonesia--Bali Island -- Interior decoration -- Architecture, Domestic